ANALYSIS OF THE PREVALENCE OF EXCLUSIVE AND MIXED BREASTFEEDING IN INFANTS YOUNGER THAN 4 MONTHS ATTENDED IN PRIMARY CARE IN MACAÉ, IN 2013 (Fiep Bulletin - online, 2016)
Feeding practices of children in their first months of life are crucial for the construction of eating habits, and breast milk the essential nourishment for the growth and development of infants up to 6 months. This study aimed to describe the prevalence of mixed breastfeeding in children
Keywords: Breastfeeding; Exclusive Breastfeeding; Child Health.